2013
DOI: 10.1007/s10464-012-9565-z
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Context in Community‐Based Participatory Research: “Participatory Starting Points” in a Chinese Immigrant Worker Community

Abstract: Community-based participatory research (CBPR) is increasingly being used to better understand and improve the health of diverse communities. A key strength of this research orientation is its adaptability to community contexts and characteristics. To date, however, few studies explicitly discuss adaptations made to CBPR principles and processes in response to community context and partners' needs. Using data from our CBPR study, the San Francisco Chinatown Restaurant Worker Health and Safety Project, and drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…26 The partnership evaluation consisted of observations, interviews, and surveys with study partners. 27 Study protocols and data collection instruments were approved by UC Berkeley's Institutional Review Board.…”
Section: The Studymentioning
confidence: 99%
See 4 more Smart Citations
“…26 The partnership evaluation consisted of observations, interviews, and surveys with study partners. 27 Study protocols and data collection instruments were approved by UC Berkeley's Institutional Review Board.…”
Section: The Studymentioning
confidence: 99%
“…Although a detailed presentation of the study findings is beyond the scope of this paper and is available elsewhere, 3,14,[25][26][27] we highlight here those of most relevance to workers, particularly in relation to their primary concerns, wage theft, and other basic worker rights violations. Survey results (n0405) indicated that almost 60 % of participants had experienced wage theft in at least one of its forms.…”
Section: Study Findingsmentioning
confidence: 99%
See 3 more Smart Citations